High-medium-low-entropy carbide nano material and preparation method thereof

By mixing the transition metal halide and carbon source with solvent and preparing it under low temperature and normal pressure through sol-gel technology, the problems of high-temperature sintering and large grain size in the existing technology are solved, and high-performance high-medium-low entropy are successfully synthesized Carbide nanomaterials.

CN119461373APending Publication Date: 2025-02-18JINGDEZHEN CERAMIC UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411668219.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-02-18

Smart Images

  • Figure CN119461373A_ABST
    Figure CN119461373A_ABST
Patent Text Reader

Abstract

The invention provides a high-medium-low-entropy carbide nano material and a preparation method thereof, and belongs to the technical field of nano materials. The preparation method comprises the following steps: taking transition metal halide and a carbon source as raw and auxiliary materials, dissolving the metal source and the carbon source by a solvent, adjusting the pH value by an alkaline solution, performing sol-gel, drying, cleaning and centrifuging by using ethanol and deionized water, and performing secondary drying to obtain a carbide precursor; and calcining the carbide precursor in vacuum to obtain the transition metal carbide nano-powder with fine grain size, uniform distribution, regular morphology and particle size of 30-100nm. According to the method, the carbide nano-powder can be synthesized at low temperature and normal pressure, the preparation process is simple, the production cost is low, and industrial production is easy to realize.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of nanomaterials, and in particular relates to a high, medium and low entropy carbide nanomaterial and a preparation method thereof. Background Art

[0002] Transition metal carbides are widely used in aerospace, cutting tools, catalysis, energy storage, biomedicine, nuclear reactors and other fields due to their high melting point, high hardness, strong oxidation and corrosion resistance, good thermal stability, good mechanical stability, and good ionic conductivity. Compared with other oxides and borides, transition metal carbides have outstanding high melting points, especially hafnium carbide (HfC) and tantalum carbide (TaC), whose melting points exceed 3800°C, so they are widely used in high temperature fields. Transition metal carbides also exhibit excellent catalytic properties. For example, Mo2C, TaC, NbC, etc. all have superconducting properties, which provides more possibilities for them in catalysis, electronics and other fields. With the development of nanotechnology, the application of transition metal carbides in fields such as electrochemical energy storage is also expanding. In short, transition metal carbides have become a hot material for research and application in many fields.

[0003] There are four main methods for preparing transition metal carbides: (1) Mechanical synthesis method, in which metal powder and carbon source (graphite or activated carbon, etc.) are ball-milled to promote solid-state diffusion and reaction between metal and carbon to form carbides. This method does not require the addition of additional chemical reagents, can reduce pollution, and is low-cost and suitable for large-scale production, but it also has limitations, such as long ball-milling time and uneven mixing. (2) Direct carbonization method, in which transition metals or their oxides and carbon sources (graphite, carbon black or activated carbon, etc.) are directly reacted at high temperature under the protection of inert gas to form carbides. This method has the advantages of low production cost, simple process and high product purity. Its disadvantages are that the required sintering temperature is relatively high, generally 1700~2000℃, and the grain size is too large. (3) Chemical vapor deposition method, in which metal source gas and carbon source gas are reacted to deposit the reactants on the substrate to undergo chemical reaction to obtain solid film-like carbides. This method can prepare extremely high-purity carbides, but the yield is low and the cost is high. (4) Self-propagating high temperature synthesis method, which uses high-purity metal powder to react chemically with carbon powder at high temperature and releases heat to maintain the reaction and finally obtain carbide. This method can complete the reaction in a very short time, and the method is simple to operate and easy to control, but it has high requirements for raw materials and the equipment is expensive. Summary of the invention

[0004] In order to solve the above problems, the present invention provides a method for preparing high, medium and low entropy carbide nanomaterials. The method can synthesize high, medium and low entropy carbide nanomaterials with small grain size and stable performance at low temperature and normal pressure.

[0005] Specifically, the present invention adopts the following technical solutions to achieve the above objectives: A method for preparing high, medium and low entropy carbide nanomaterials comprises the following steps: S1, mixing the transition metal halide and the carbon source with the solvent respectively, and then mixing the two to form a mixed solution; S2, adding an alkaline solution to the mixed solution to adjust the pH value to promote sol-gelation, and then drying it once, then adding ethanol and deionized water for washing and centrifugation, and drying it twice to obtain a carbide precursor; S3, calcining the carbide precursor under vacuum, and then cooling naturally to obtain transition metal carbide nanopowder; the transition metal halide is a metal of Group IVB, Group VB or Group VIB.

[0006] In a preferred technical solution of the present invention, the molar ratio of the transition metal halide to the carbon source is (1-5):1.

[0007] In a further preferred technical solution of the present invention, the molar ratio of the transition metal halide to the carbon source is (2-3):1.

[0008] In a preferred technical solution of the present invention, the molar ratio of the transition metal halide to the solvent is (1-5):0.034.

[0009] In a further preferred technical solution of the present invention, the molar ratio of the transition metal halide to the solvent is (2-3):0.034.

[0010] In a preferred technical solution of the present invention, the molar ratio of the alkaline solution to the transition metal halide is (0.0017~0.0056):1.

[0011] In a further preferred technical solution of the present invention, the molar ratio of the alkaline solution to the transition metal halide is (0.0017~0.0044):1.

[0012] In a preferred technical solution of the present invention, the transition metal halide is a transition metal chloride.

[0013] In a further preferred technical solution of the present invention, the transition metal halide is any one or more combination systems of titanium tetrachloride, zirconium tetrachloride, hafnium tetrachloride, niobium pentachloride, tantalum pentachloride, chromium trichloride and molybdenum pentachloride.

[0014] In a preferred technical solution of the present invention, the carbon source is any one of pyromellitic acid, acetylacetone and furfuryl alcohol.

[0015] In a preferred technical solution of the present invention, the solvent is at least one of ethanol, acetic acid, and deionized water.

[0016] In a preferred technical solution of the present invention, the alkaline solution is at least one of NaOH solution, KOH solution, and ammonia water.

[0017] In a preferred technical solution of the present invention, the primary drying in step S2 refers to keeping the mixed gel at 100-150° C. for 12-18 hours. In a preferred technical solution of the present invention, the temperature of the secondary drying in step S2 is 100-150° C. and maintained for 8-16 hours.

[0018] In a preferred technical solution of the present invention, the centrifugal speed in step S2 is 8000-10000 rpm, and the centrifugal time is 3-5 min.

[0019] In a preferred technical solution of the present invention, the calcination in step S3 refers to maintaining the temperature at 1300-1600° C. for 1-2 hours.

[0020] The present invention also provides a high, medium and low entropy metal carbide nanomaterial prepared by the preparation method described in any one of the above technical solutions. The transition metal carbide nanomaterial has fine and uniform grains with a particle size of 30-100 nm.

[0021] Compared with the prior art, the technical solution of the present invention has the following beneficial effects: BRIEF DESCRIPTION OF THE DRAWINGS Figure 1 This is a SEM image of the ZrC nanopowder prepared in Example 1 of the present invention; Figure 2 This is a TEM image of the ZrC nanopowder prepared in Example 1 of the present invention; Figure 3 This is the XRD pattern of the ZrC nanopowder prepared in Example 1 of the present invention; Figure 4 This is a SEM image of the (ZrHfNb)C nanopowder prepared in Example 2 of the present invention; Figure 5 TEM image of (ZrHfNb)C nanopowder prepared in Example 2 of the present invention; Figure 6 This is the XRD pattern of the (ZrHfNb)C nanopowder prepared in Example 2 of the present invention; Figure 7 TG-DTA graph of (ZrHfNb)C nanopowder prepared in Example 2 of the present invention; Figure 8 This is a SEM image of the (TiZrTa)C nanopowder prepared in Example 3 of the present invention; Fig. 9TEM image of (TiZrTa)C nanopowder prepared in Example 3 of the present invention; Fig.10 This is the XRD pattern of the (TiZrTa)C nanopowder prepared in Example 3 of the present invention; Fig.11 TG-DTA diagram of (TiZrTa)C nanopowder prepared in Example 3 of the present invention; Fig.12 This is a SEM image of the (CrZrNbTa)C nanopowder prepared in Example 4 of the present invention; Fig.13 TEM image of (CrZrNbTa)C nanopowder prepared in Example 4 of the present invention; Fig.14 This is the XRD pattern of the (CrZrNbTa)C nanopowder prepared in Example 4 of the present invention; Fig.15 This is the TG-DTA graph of the (CrZrNbTa)C nanopowder prepared in Example 4 of the present invention; Fig.16 This is a SEM image of the (TiZrHfTa)C nanopowder prepared in Example 5 of the present invention; Fig.17 TEM image of (TiZrHfTa)C nanopowder prepared in Example 5 of the present invention; Fig.18 This is the XRD pattern of the (TiZrHfTa)C nanopowder prepared in Example 5 of the present invention; Fig.19 This is the TG-DTA graph of the (TiZrHfTa)C nanopowder prepared in Example 5 of the present invention; Fig. 20 This is a SEM image of the (TiZrHfNbMo)C nanopowder prepared in Example 6 of the present invention; Fig.21 TEM image of (TiZrHfNbMo)C nanopowder prepared in Example 6 of the present invention; Fig. 22 This is the XRD pattern of the (TiZrHfNbMo)C nanopowder prepared in Example 6 of the present invention; Fig.23 This is the TG-DTA graph of the (TiZrHfNbMo)C nanopowder prepared in Example 6 of the present invention. DETAILED DESCRIPTION

[0022] The following content is combined with the embodiments to clearly and completely describe the technical solution of the present application so that those skilled in the art can fully understand the present application. Obviously, the described embodiments are only some preferred embodiments of the present application, rather than all embodiments. Any equivalent transformation or substitution made to the following implementation modes by those of ordinary skill in the art without creative work belongs to the protection scope of the present application.

[0023] The titanium tetrachloride, zirconium tetrachloride, hafnium tetrachloride, niobium pentachloride, tantalum pentachloride, chromium trichloride, molybdenum pentachloride, pyromellitic acid, acetylacetone, furfuryl alcohol, ethanol, acetic acid, sodium hydroxide, potassium hydroxide, ammonia water and other reagents used in the following examples are all chemically pure and can be purchased through commercial channels.

[0024] Example 1 This embodiment provides a method for preparing a low entropy ZrC nanomaterial, comprising the following steps: S1. Mix zirconium tetrachloride and acetic acid in equal molar ratios, then mix furfuryl alcohol and acetic acid, and then mix the two to form a mixed solution; the molar ratio of furfuryl alcohol to zirconium tetrachloride is 1:2, and the molar ratio of acetic acid to zirconium tetrachloride is 0.034:2.

[0025] S2. Add KOH solution to the mixed solution in step S1 to promote its sol-gel, put it in an oven, and dry it at 120°C for 18 hours. Add the dried product to ethanol (the amount of ethanol is sufficient to prepare the dried product into a suspension) and deionized water (the amount of deionized water is sufficient to prepare the dried product into a suspension), and centrifuge at 8000rpm for 5 minutes; repeat 3 times. Put the solid after centrifugation into an oven and dry it at 120°C for 16 hours to obtain a ZrC precursor; the molar ratio of KOH solution to the mixed solution is 0.0017:1.

[0026] S3. The ZrC precursor obtained in step S2 is placed in a multifunctional sintering furnace and calcined at 1300° C. for 1 hour, followed by natural cooling to obtain ZrC nanopowder.

[0027] The scanning electron microscope (SEM) image of the prepared ZrC nanopowder is shown in Figure 1 As shown in the transmission electron microscope TEM image Figure 2 As shown, the X-ray diffraction (XRD) pattern is as follows Figure 3 As shown. Figure 1 and 2 It can be seen that the carbide nanopowder has fine and uniform grains with a particle size of 30-100nm; Figure 3 It can be seen that the prepared carbide powder is ZrC phase and has good crystallinity.

[0028] Example 2 This embodiment provides a method for preparing a medium entropy (ZrHfNb)C nanomaterial, comprising the following steps: S1. Mix zirconium tetrachloride, hafnium tetrachloride and niobium pentachloride in equal molar ratios with ethanol, then mix pyromellitic acid with ethanol, and then mix the two to prepare a mixed solution; the molar ratio of pyromellitic acid to transition metal halide is 1:2, and the molar ratio of ethanol to transition metal halide is 0.034:2.5.

[0029] S2. Add NaOH solution to the mixed solution in step S1 to promote its sol-gel, put it in an oven, and dry it at 120°C for 16 hours. Add the dried product to ethanol (the amount of ethanol is sufficient to prepare the dried product into a suspension) and deionized water (the amount of deionized water is sufficient to prepare the dried product into a suspension), and centrifuge at 9000rpm for 5 minutes; repeat 3 times. Put the solid after centrifugation into an oven and dry it at 120°C for 12 hours to obtain the (ZrHfNb)C precursor; the molar ratio of NaOH solution to the mixed solution is 0.003:1.

[0030] S3. The (ZrHfNb)C precursor obtained in step S2 is placed in a multifunctional sintering furnace and calcined at 1400° C. for 1 hour, followed by natural cooling to obtain (ZrHfNb)C nanopowder.

[0031] The scanning electron microscope (SEM) image of the prepared (ZrHfNb)C nanopowder is shown in Figure 4 As shown in the transmission electron microscope TEM image Figure 5 As shown, the X-ray diffraction (XRD) pattern is as follows Figure 6 As shown, the thermogravimetric-differential thermal analysis TG-DTA diagram is as follows Figure 7 As shown. Figure 4 and 5 It can be seen that the carbide nanopowder has fine and uniform grains, with a particle size of 50-100nm; Figure 6 It can be seen that the prepared carbide powder is (ZrHfNb)C phase with good crystallinity; Figure 7 It can be seen that (ZrHfNb)C nanopowders can be prepared by carbothermal reduction at 1400°C.

[0032] Example 3 This embodiment provides a method for preparing a medium entropy (TiZrTa)C nanomaterial, comprising the following steps: S1. Mix titanium tetrachloride, zirconium tetrachloride and tantalum pentachloride in equal molar ratios with ethanol, then mix pyromellitic acid with ethanol, and then mix the two to form a mixed solution; the molar ratio of pyromellitic acid to transition metal halide is 1:2.5, wherein the molar ratio of ethanol to transition metal halide is 0.034:2.5.

[0033] S2. Add NaOH solution to the mixed solution in step S1 to promote its sol-gel, put it in an oven, and dry it at 120°C for 18 hours. Add the dried product to ethanol (the amount of ethanol is sufficient to prepare the dried product into a suspension) and deionized water (the amount of deionized water is sufficient to prepare the dried product into a suspension), and centrifuge at 9000rpm for 5 minutes; repeat 3 times. Put the solid after centrifugation into an oven and dry it at 120°C for 12 hours to obtain a (TiZrTa)C precursor; the molar ratio of NaOH solution to the mixed solution is 0.003:1.

[0034] S3. The (TiZrTa)C precursor obtained in step S2 is placed in a multifunctional sintering furnace and calcined at 1400° C. for 1 hour, followed by natural cooling to obtain (TiZrTa)C nanopowder.

[0035] The scanning electron microscope (SEM) image of the prepared (TiZrTa)C nanopowder is shown in Figure 8 As shown in the transmission electron microscope TEM image Fig. 9 As shown, the X-ray diffraction (XRD) pattern is as follows Fig.10 As shown, the thermogravimetric-differential thermal analysis TG-DTA diagram is as follows Fig.11 As shown. Figure 8 and 9 It can be seen that the carbide nanopowder has fine and uniform grains with a particle size of 30-100nm; Fig.10 It can be seen that the prepared carbide powder is (TiZrTa)C phase with good crystallinity; Fig.11 It can be seen that (TiZrTa)C nanopowder can be prepared by carbothermal reduction at 1400°C.

[0036] Example 4 This embodiment provides a method for preparing a high entropy (CrZrNbTa)C nanomaterial, comprising the following steps: S1. Mix chromium trichloride, zirconium tetrachloride, niobium pentachloride and tantalum pentachloride in equal molar ratios with deionized water, then mix acetylacetone with deionized water, and then mix the two to form a mixed solution; the molar ratio of acetylacetone to transition metal halide is 1:3, wherein the molar ratio of deionized water to transition metal halide is 0.034:3.

[0037] S2. Add ammonia water to the mixed solution in step S1 to promote its sol-gel, put it in an oven, and dry it at 120°C for 20 hours. Add the dried product to ethanol (the amount of ethanol is sufficient to prepare the dried product into a suspension) and deionized water (the amount of deionized water is sufficient to prepare the dried product into a suspension), and centrifuge at 10000rpm for 3min; repeat 3 times. Put the solid after centrifugation into an oven and dry it at 120°C for 16h to obtain the (CrZrNbTa)C precursor; the molar ratio of ammonia water to the mixed solution is 0.004:1.

[0038] S3. The (CrZrNbTa)C precursor obtained in step S2 is placed in a multifunctional sintering furnace and calcined at 1500° C. for 1.5 h, followed by natural cooling to obtain (CrZrNbTa)C nanopowder.

[0039] The scanning electron microscope (SEM) image of the prepared (CrZrNbTa)C nanopowder is shown in Fig.12 As shown in the transmission electron microscope TEM image Fig.13 As shown, the X-ray diffraction (XRD) pattern is as follows Fig.14 As shown, the thermogravimetric-differential thermal analysis TG-DTA diagram is as follows Fig.15 As shown. Fig.12 and 13 It can be seen that the carbide nanopowder has fine and uniform grains with a particle size of 30-100nm; Fig.14 It can be seen that the prepared carbide powder is (CrZrNbTa)C phase with good crystallinity; Fig.15 It can be seen that (CrZrNbTa)C nanopowder can be prepared by carbothermal reduction at 1500°C.

[0040] Example 5 This embodiment provides a method for preparing a high entropy (TiZrHfTa)C nanomaterial, comprising the following steps: S1. Mix titanium tetrachloride, zirconium tetrachloride, hafnium tetrachloride and tantalum pentachloride in equal molar ratios with deionized water, then mix acetylacetone with deionized water, and then mix the two to form a mixed solution; the molar ratio of acetylacetone to transition metal halide is 1:3, wherein the molar ratio of deionized water to transition metal halide is 0.034:3.

[0041] S2. Add ammonia water to the mixed solution in step S1 to promote its sol-gel, put it in an oven, and dry it at 120°C for 18 hours. Add the dried product to ethanol (the amount of ethanol is sufficient to prepare the dried product into a suspension) and deionized water (the amount of deionized water is sufficient to prepare the dried product into a suspension), and centrifuge at 8000rpm for 5 minutes; repeat 3 times. Put the solid after centrifugation into an oven and dry it at 120°C for 12 hours to obtain a (TiZrHfTa)C precursor; the molar ratio of ammonia water to the mixed solution is 0.004:1.

[0042] S3. The (TiZrHfTa)C precursor obtained in step S2 is placed in a multifunctional sintering furnace and calcined at 1500° C. for 1 hour, followed by natural cooling to obtain (TiZrHfTa)C nanopowder.

[0043] The scanning electron microscope (SEM) image of the prepared (TiZrHfTa)C nanopowder is shown in Fig.16 As shown in the transmission electron microscope TEM image Fig.17 As shown, the X-ray diffraction (XRD) pattern is as follows Fig.18 As shown, the thermogravimetric-differential thermal analysis TG-DTA diagram is as follows Fig.19 As shown. Fig.16 and 17 It can be seen that the carbide nanopowder has fine and uniform grains with a particle size of 30-100nm; Fig.18 It can be seen that the prepared carbide powder is (TiZrHfTa)C phase with good crystallinity; Fig.19 It can be seen that (TiZrHfTa)C nanopowders can be prepared by carbothermal reduction at 1500°C.

[0044] Example 6 This embodiment provides a method for preparing a high entropy (TiZrHfNbMo)C nanomaterial, comprising the following steps: S1. Mix titanium tetrachloride, zirconium tetrachloride, hafnium tetrachloride, niobium pentachloride and molybdenum pentachloride in equal molar ratios with acetic acid, mix furfuryl alcohol with acetic acid, and then mix the two to form a mixed solution; the molar ratio of furfuryl alcohol to transition metal halide is 1:2.5, wherein the molar ratio of acetic acid to transition metal halide is 0.034:2.5.

[0045] S2. Add KOH solution to the mixed solution in step S1 to promote its sol-gel, put it in an oven, and dry it at 120°C for 20 hours. Add the dried product to ethanol (the amount of ethanol is sufficient to prepare the dried product into a suspension) and deionized water (the amount of deionized water is sufficient to prepare the dried product into a suspension), and centrifuge at 9000rpm for 5min; repeat 3 times. Put the solid after centrifugation into an oven and dry it at 120°C for 16h to obtain the (TiZrHfNbMo)C precursor; the molar ratio of KOH solution to the mixed solution is 0.004:1.

[0046] S3. The (TiZrHfNbMo)C precursor obtained in step S2 is placed in a multifunctional sintering furnace and calcined at 1600° C. for 1 hour, followed by natural cooling to obtain (TiZrHfNbMo)C nanopowder.

[0047] The scanning electron microscope (SEM) image of the prepared (TiZrHfNbMo)C nanopowder is shown in Fig. 20 As shown in the transmission electron microscope TEM image Fig.21 As shown, the X-ray diffraction (XRD) pattern is as follows Fig. 22 As shown, the thermogravimetric-differential thermal analysis TG-DTA diagram is as follows Fig.23 As shown. Fig. 20 and 21 It can be seen that the carbide nanopowder has fine and uniform grains, with a particle size of 50-100nm; Fig. 22 It can be seen that the prepared carbide powder is (TiZrHfNbMo)C phase with good crystallinity; Fig.23 It can be seen that (TiZrHfNbMo)C nanopowders can be prepared by carbothermal reduction at 1600°C.

[0048] The above-described embodiments are only preferred embodiments of the present application and are not intended to limit the scope of protection of the present application. For any person skilled in the art, the present application may have various changes and modifications. Any simple equivalent changes and modifications made based on the scope of protection of the present application and the contents of the specification should be included in the scope of protection of the present application.

Claims

1. A method for preparing high, medium and low entropy carbide nanomaterials, characterized in that: The following steps are involved: S1, mixing the transition metal halide and the carbon source with the solvent respectively, and then mixing the two to form a mixed solution; S2, adding an alkaline solution to the mixed solution to adjust the pH value to promote sol-gelation, and then drying it once, then adding ethanol and deionized water for washing and centrifugation, and drying it twice to obtain a carbide precursor; S3, calcining the carbide precursor under vacuum, and then cooling naturally to obtain transition metal carbide nanopowder; the transition metal halide is a metal of Group IVB, Group VB or Group VIB.

2. The method for preparing high, medium and low entropy carbide nanomaterials according to claim 1, characterized in that: The molar ratio of the transition metal halide to the carbon source is (1-5):

1.

3. The method for preparing high, medium and low entropy carbide nanomaterials according to claim 1, characterized in that: The molar ratio of the transition metal halide to the solvent is (1-5):0.

034.

4. The method for preparing high, medium and low entropy carbide nanomaterials according to claim 1, characterized in that: The molar ratio of the alkaline solution to the transition metal halide is (0.0017-0.0056):

1.

5. The method for preparing high, medium and low entropy carbide nanomaterials according to claim 1, characterized in that: The transition metal halide is a unit to multi-component combination system of titanium tetrachloride, zirconium tetrachloride, hafnium tetrachloride, niobium pentachloride, tantalum pentachloride, chromium trichloride and molybdenum pentachloride.

6. The method for preparing high, medium and low entropy carbide nanomaterials according to claim 1, characterized in that: The carbon source is at least one of pyromellitic acid, acetylacetone and furfuryl alcohol.

7. The method for preparing high, medium and low entropy carbide nanomaterials according to claim 1, characterized in that: The solvent is at least one of ethanol, acetic acid and deionized water.

8. The method for preparing high, medium and low entropy carbide nanomaterials according to claim 1, characterized in that: The alkaline solution is at least one of a NaOH solution, a KOH solution, and an ammonia solution.

9. The method for preparing high, medium and low entropy carbide nanomaterials according to claim 1, characterized in that: The primary drying in step S2 refers to keeping the mixed sol at 100-150°C for 16-24 hours; or / and the secondary drying in step S2 is at 100-150°C for 16-24 hours; or / and the calcination in step S3 refers to keeping at 1300-1600°C for 1-2 hours.

10. The high, medium and low entropy carbide nanomaterial prepared by the preparation method according to any one of claims 1 to 9.